National Information Infrastructure and the realization of Singapore IT2000 initiative - Cheryl Marie Cordeiro; Suliman Al-Hawamdeh (Information Research: An International Electronic Journal)
Being a small island and without any natural resource, Singapore has much to depend on its human potential and investment in National Information Infrastructure (NII) in order to find its place in the ever competitive global world economies. From Singapore's first experience with the setting up and accessing of the Internet in 1991, the Singapore Government has expended so much creative and financial energy into using information technology to spearhead Singapore's success in terms of enticing and encouraging economic growth and achieving national competitiveness on a global scale. In 1991, the Singapore government, together with the National Computer Board (NCB) currently known as the Infocomm Development Authority (IDA), launched the IT 2000, with the objective of converting Singapore into an intelligent island. With many NII projects in place and the various government initiative, this study focus on the role of Singapore Government in the development of the national information infrastructure and the realisation of IT2000 vision. This investigative study delves into the role of the Singapore government in helping Singapore forge its path into the new millennium of the information world.